BASIC PRINCIPLES AND ISSUES OF STATE REGULATION OF SOCIAL AND LABOR RELATIONS IN UKRAINE - Nazarenko O.M. (Pressing Problems of Public Administration, 2016)
Considered and singled out the basic principles of state regulation of social and labor relations inUkraine. The analysis of the main problems of state regulation of social and labor relations in Ukrainein conditions of modernity. Overview of scienti c and theoretical approaches to de ning the essenceof industrial relations, imposed reason that the need to actualize their study in the current socioeconomicconditions of society.